Which Brazilian policy for regionalism? Discourse and institutional development in Mercosur - de Almeida Medeiros, Marcelo; Franzoi Dri, Clarissa (Estudios Internacionales, 2013)
During the past decade, Mercosur has been insistently presented as the priority of Brazilian foreign policy. Nevertheless, in this period regional integration has neither deepened nor enlarged. This article aims to explain this gap between discourse and practice by examining how Brazil's regionalism policy is characterized. The analysis is based on a case study of the creation of Mercosur's Parliament in 2006. Theoretically, we argue that discursive institutionalism and international regimes theory can largely account for the detachment of Brazil from Mercosur and the limited interdependence that has been built among these countries. The conclusion points to the induction of a low-impact regionalism that facilitates Brazil's actions at the international level.